Macroeconomic Factors and Bank Risk - Esteban Prieto; Claudia M. Buch; Sandra Eickmeier (Verein für Socialpolitik, 2010)
The interplay between banks and the macroeconomy is of key importance for financial and economic stability. We analyze this link using a Factor Augmented Vector Autoregressive Model (FAVAR) which extends a standard VAR for the U.S. macroeconomy with a set of factors summarizing conditions in the banking sector. We use the model to analyze bank risk, bank returns, and bank lending. We take data of more than 2,000 commercial banks from the U.S. Call Reports. We assess the importance of common versus idiosyncratic risk at the bank level and the heterogeneous transmission of macroeconomic and asset price shocks to individual banks. Our paper has four main findings. First, average bank risk declines following expansionary shocks. Results for individual banks reveal that 1/3 of all banks increase risk after a monetary loosening. In this sense, our results are partly in support of the risk-taking channel. Second, bank lending increases following expansionary shocks. Third, the correlation between bank risk and return depends on the underlying macroeconomic shock. Fourth, banks' responses to macroeconomic shocks exhibit a high degree of heterogeneity. We find that riskiness and internationalization are determinants of banks' risk and lending exposure to monetary policy shocks, and that liquidity, in addition, determines banks' lending exposure.
Keywords: E44; G21; G20; 330; FAVAR; monetary policy; risk-taking channel; lending channel; banking